LANGUAGE AND ITS RELATIONSHIP TO RELIGIOSITY - Sufrin Efendi Lubis (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
Language serves as a means of communication among humans. Through language, individuals express their preferences and dislikes, as well as offer praise or criticism to others. This highlights the significant role language plays in a person's life, as it can bring respect or subject them to insult. Accordingly, there is an intrinsic relationship between language—particularly spoken language—and religiosity. This research aims to explore spoken language specifically, as the researcher will focus extensively on how individuals use speech to convey their intentions. The central research question is: